ChemInform Abstract: Enantioselective Total Synthesis of the Proposed Structure of the Endophytic Fungal Metabolite Phomolide G: Structural Revision and Unambiguous Stereochemical Assignment. Issue 25 (June 2016) - McNulty, James; McLeod, David; Jenkins, Hilary A.
Abstract: The synthesis of the proposed structure of phomolide G (I) from L‐tartaric acid shows significant differences in the NMR data with the natural product.